A Sensitive Method for Detecting Variation in Copy Numbers of Duplicated Genes - Pielberg, Gerli; Day, Andy E.; Plastow, Graham S.; Andersson, Leif (Genome Research, 2003)
Gene duplications are common in the vertebrate genome, and duplicated loci often show a variation in copy number that may have important phenotypic effects. Here we describe a powerful method for quantification of duplicated copies based on pyrosequencing. A reliable quantification was obtained by amplification of the duplication break-point and a corresponding nonduplicated sequence in a competitive PCR assay. A comparison with an independent method for quantification based on the Invader technology revealed an excellent correlation between the two methods. The pyrosequencing-based method was evaluated by analyzing variation in copy number at the duplicated KIT/Dominant white locus in pigs. We were able to distinguish haplotypes at this locus by combining the duplication breakpoint test with a diagnostic test for a functionally important splice mutation in the duplicated gene. An extensive allelic variation, including the presence of a new allele carrying a single KIT copy expected to encode a truncated KIT receptor, was revealed when analyzing white pigs from commercial lines.
10.1101/gr.1188203